An Innovative Model for the Sustainability of Investments in the Wind Energy Sector: The Use of Green Sukuk in an Italian Case Study - Morea, Donato; Poggi, Luigi Antonio (International Journal of Energy Economics and Policy, 2017)
In this paper we present the technical-energy-economic feasibility of wind power systems. An Italian 1 Megawatt (MW) case study was considered to evaluate the importance of incentives in order to achieve the grid parity. Due to the severe reduction of incentives in the last years, in the present work we propose the use of Sukuk, a Shari'ah-compliant instrument used in the Islamic Finance, as an alternative financial instrument used to limit the extent of leverage associated with financing. The building cost thresholds necessary to achieve the grid parity and a profitable and bankable project are presented with a sensitivity analysis. In the framework of the efforts against climate change and the emission of greenhouse gas (GHG), our results evidenced the importance of incentives and the applicability of the use of Shari'ah-compliant sukuk instruments in order to provide a feasible and sustainable investment in the wind energy sector. Keywords: wind energy, grid parity, green sukuk JEL Classifications: Q420, L940, P480